Term Limits, the Standing Committees, and Institutional Response - Moen, Matthew; Palmer, Kenneth (Maine Policy Review, 2002)
Through citizen initiative in 1993, Maine passed a term limits bill that now prevents legislators with eight years of consecutive service from seeking reelection. Although touted as a means of eliminating careerism in public service and as a means of bringing fresh blood and new policy initiative to Augusta, many now question whether limits on service have hampered legislative efficiency through the loss of experienced leadership and institutional memory. Moen and Palmer examine the impact of term limits on the legislature’s standing committees. While noting adverse impacts such as heavier workloads, they also find an institution hard at work to adapt, with leadership seeking new ways to improve operations and to orient new members to a rapidly changing environment.